2008
DOI: 10.30843/nzpp.2008.61.6814
|View full text |Cite
|
Sign up to set email alerts
|

European earwig as a potential biological control agent of apple leafcurling midge

Abstract: The European earwig Forficula auricularia L is an important predator of aphids and scales in New Zealand apple orchards To determine whether European earwig acted as a biological control agent of apple leafcurling midge (ALCM) Dasineura mali Kieffer their prey searching and feeding activity was investigated in the field and laboratory In the field in January earwigs started to leave their shelters at about 920 pm to search for ALCM larvae and returned to the shelters before 535 am with a searching peak on appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Previous work has shown that, at least in its native range, F. auricularia is a potentially important biological control agent of various pests in orchards including leaf‐curling midges and aphids (He, Wang, & Xu, ; Mueller, Blommers, & Mols, ; Nicholas, Spooner‐Hart, & Vickers, ). Various methods to augment the overwintering survival of earwigs in orchards have been described (Carroll & Hoyt, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that, at least in its native range, F. auricularia is a potentially important biological control agent of various pests in orchards including leaf‐curling midges and aphids (He, Wang, & Xu, ; Mueller, Blommers, & Mols, ; Nicholas, Spooner‐Hart, & Vickers, ). Various methods to augment the overwintering survival of earwigs in orchards have been described (Carroll & Hoyt, ).…”
Section: Discussionmentioning
confidence: 99%
“…1988; Nicholas et al. 2005) and midges (He et al. 2008) in apple orchards, psyllids in pear orchards (Höhn et al.…”
Section: Discussionmentioning
confidence: 99%
“…According to Lordan et al ( 2014 ), the shelters were prepared by rolling a piece of corrugated cardboard into a cylinder (12 cm height×9 cm diameter), which was protected from rain and adverse conditions by a PVC tube (15 cm height×9.5 cm diameter). Similar shelters have been used in studies of European earwigs elsewhere (Phillips, 1981 ; Helsen et al , 1998 ; Solomon et al , 1999 ; Burnip et al , 2002 ; Gobin et al , 2006 ; Logan et al , 2007 ; He et al , 2008 ; Moerkens et al , 2009 ). Every week throughout the year, we counted the number of earwigs per shelter.…”
Section: Methodsmentioning
confidence: 99%